Photocatalytic H2 Generation: Controlled and Optimized Dispersion of Single Atom Co-Catalysts Based on Pt-TCPP Planar Adsorption on TiO2 - Qin, Shanshan; Denisov, Nikita; Kim, Hyesung; Schmuki, Patrik (Angewandte Chemie International Edition, 2024)
When using single atoms (SAs) as a co-catalyst in photocatalytic H2 generation, achieving a well-dispersed, evenly distributed and adjustable SA surface density on a semiconductor surface is a challenging task. In the present work we use the planar adsorption of tetrakis-(4-carboxyphenyl)-porphyrin (TCPP) and its platinum coordinated analogue, Pt-TCPP, onto anatase TiO2 surfaces to establish a spatially controlled decoration of SAs. We show that the surface Pt SA density can be very well controlled by co-adsorption of Pt-TCPP and TCPP in the planar monolayer regime, and by adjusting the Pt-TCPP to TCPP ratio a desired well dispersed surface density of SAs up to 2.6×105 atoms μm−2 can be established (which is the most effective Pt SA loading for photocatalysis). This distribution and the SA state are maintained after a thermal treatment in air, and an optimized SA density as well as a most active form of Pt for photocatalytic H2 evolution can be established and maintained.
CRIS-Team Scopus Importer:2024-02-16
Keywords: hydrogen evolution; photocatalysis; platinum; porphyrins; single-atom catalysts